Den licensierade vargjaktens betydelse för vargstammen - Kvastegård, Emma (SLU/Dept. of Ecology, 2010)

(untitled)
In October 2009, a new decision was made concerning the administration of predators which resulted in a new wolf policy in Sweden. This meant that the wolf population now should be limited to 210 individuals by harvest. The new policy also recognized that the public acceptance of this species must increase and the genetic status improved. In the 17th of December a decision was taken by the Swedish parliament that it should become legal to hunt wolves in Sweden. The wolf hunt resulted in debate on a large scale amongst people, some thought of it as a good decision while others thought it was wrong. Today the wolf is Endangered (EN) in Sweden. The purpose of this paper is to illustrate the significance of wolf harvest to the wolf population development.